Association of Nutritional Status, Sodium Intake, Family Support, and Perception of Salted Food Consumption with Hypertension in the Community of the Palangkau Primary Health Care Area - Marlina; Anwar, Rosihan; Abdurrachim, Rijanti; Mahpolah (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2026)
Hypertension is a major public health problem with an increasing prevalence and is influenced by various biological, behavioral, and social factors. Nutritional status, sodium intake, family support, and perceptions of salted food consumption are considered potential contributors to the occurrence of hypertension, particularly in communities with high-salt dietary habits. This study aimed to analyze the association of nutritional status, sodium intake, family support, and perception of salted food consumption with hypertension among community members in the working area of the Palangkau Primary Health Care Center. This study employed an observational analytic design with a cross-sectional approach. A total of 81 respondents aged 18–65 years were selected using proportional sampling. Data were collected through blood pressure measurements, anthropometric assessments to determine Body Mass Index, and structured interviews using a semi-quantitative food frequency questionnaire, family support questionnaire, and perception of salted food consumption questionnaire. Data were analyzed using univariate and bivariate analyses with the Spearman rank correlation test. The results showed that most respondents were classified as having mild hypertension, were overweight, and had poor sodium intake. Bivariate analysis indicated no significant association between nutritional status, sodium intake, family support, or perception of salted food consumption and hypertension (p > 0.05). This study concludes that hypertension is a multifactorial condition; therefore, hypertension control efforts should be implemented comprehensively through sustainable promotive and preventive approaches in primary health care services.